Re-assessing modalising expressions categories, co-text, and context - Hohaus, Pascal; Schulze, Rainer, 1952- (Studies in language companion series ;, 2020)
"Mood, modality and evidentiality are popular and dynamic areas in linguistics. Re-Assessing Modalising Expressions - Categories, co-text, and context focuses on the specific issue of the ways language users express permission, obligation, volition (intention), possibility and ability, necessity and prediction linguistically. Using a range of evidence and corpus data collected from different sources, the authors of this volume examine the distribution and functions of a range of patterns involving modalising expressions as predominantly found in standard American English, British English or Hong Kong English, but also in Japanese. The authors are particularly interested in addressing (co-)textual manifestations of modalising expressions as well as their distribution across different text-types and thus filling a gap research was unable to plug in the past. Thoughts on categorising or re-categorising modalising expressions initiate and complement a multi-perspectival enterprise that is intended to bring research in this area a step forward"--